PERAN PEREMPUAN SEPANJANG PERKEMBANGAN SEJARAH PERADABAN ISLAM - Agus Santri (Universitas Islam Negeri Sumatera Utara Medan, 2020)
Islam puts women in an honorable position, even one of the suras in the Qur'an is An-Nisa (4th surah in the Qur'an) which means